Pragmatic Communicative Patterns in New Normal Context: A Case Study of Restaurant Staff and Food and Delivery Providers - Chudkhan, Sasiwimon; sawettanun, kanlayarat (RMUTL Journal of Socially Engaged Scholarship, 2023)
ABSTRACT This research aimed at studying and analyzing the needs of pragmatic English communicative patterns based on Pragmatic Function of Grice's Maxims, then designing language models in the new normal context for restaurant staff and food and delivery providers. This research was qualitative, and the purposive samples were 50 restaurant staff and food delivery service providers in Chiang Mai. The research instruments were an observation, a semi-structured interview, an English for communication needs questionnaire, English language models in a new normal context, and satisfaction on an English language models questionnaire relating to pragmatic communicative patterns. The finding revealed that restaurant staff and food delivery service providers needed to develop language for expressing thanks and leave-taking, informing food prices and payment methods, and asking for repetitions, respectively. Consequently, two models were designed and evaluated. It was found that the satisfaction was at the most highly satisfied level. The language employed was current, precise, and accurate to align with the new normal context, facilitating self-practice in daily communication and ultimately improving their service quality. Keywords: Pragmatic communicative patterns, New normal context, Restaurant Staff, Food and delivery provider